Indeks Kinerja Keuangan Perusahaan Yang Tergabung Dalam Indeks Saham LQ45 Pada Masa Pandemi Covid-19 - Wibowo, Bayu Teguh; Nurrofi, Akhmad; Mahmud, Nuruddin (Innovative: Journal Of Social Science Research, 2024)
The Covid-19 pandemic has ended and made many changes and performance, especially in business, but there is still a lot to study about company performance during the pandemic to create experience in business. This research is a way of interpreting company financial performance through financial ratios of liquidity, profitability and solvency carried out on companies included in the LQ45 stock index from 2020 to 2022. After conducting qualitative and quantitative analysis of primary data, the results showed that although there were still 8 companies with performance is lacking but that does not make the index performance decrease, on the contrary the overall financial ratio index is good and tends to increase.